Forecasting, preparedness and other operational measures for water-related natural disaster reduction in Asia and the Pacific (United Nations New YorkUS, 1990)
Includes the report of the Workshop on the above mentioned topics, the notes on presentations of four lectures and three case studies, as well as an assessment of preparedness measures for water-related natural disasters in the ESCAP region.
Includes bibliography